Identification of Pathogenicity of Yersinia enterocolitica in Pig Tonsils Using the Real-Time PCR - MILENA A. STACHELSKA (Polish Journal of Microbiology, 2018)
The application of DNA-based methods enables to identify Yersinia enterocolitica carrying the ail-gene with a greater sensitivity compared to culture methods and biochemical tests used for detection of pathogenic Y. enterocolitica in animal and food samples. In this study, 100 samples of pig tonsils were examined, among which 17 were positive for the ail gene. Additionally, biochemical tests and RT-PCR showed that nine Y. enterocolitica isolates carried the ail-gene. Two Y. enterocolitica isolates of 1A biotype had the ail gene. The results demonstrated the usefulness of RT-PCR method applied for detection of potentially pathogenic, possessing the ail gene Y. enterocolitica in the material examined.